Family and community in and out of the classroom: Ways to improve mathematics? achievement - Díez-Palomar, Javier (Congressos, 2012)
Family and community in and out of the classroom introduce the reader to the field of family engagement in mathematics teaching and learning processes. Scientific evidence collected by the European Union throughout many different studies in a number of research programs, highlights researchers' increasing interest for the role that families play in the process of learning. There is a set of evidence demonstrating the positive impact of family engagement and students' performance. In this book we collect the main findings achieved in the frame of FAMA - Family Math for Adult Learners. Drawing on these results, it seems clear that activities conducted in and out of the classroom have a strong impact on students' scores in mathematics. Throughout this book, the reader will find what are the main trends in mathematics family education in Europe and other World regions, as well as what are the more successful actions in this field.